Policy Analysis of the Termination of Football Competitions in the Time of the Covid-19 Pandemic - Angga Wijaya; Sandey Tantra Paramitha; Mustika Fitri (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The purpose of this study was to determine the impact of the policy of Termination of Football Competitions during the Covid 19 Pandemic which was issued by PSSI for clubs and players. The research was conducted using a qualitative method, where semi-structured interview data were collected from participants, such as data from direct observations of participants and documentation studies. Data analysis was continued using triangulation. The results of this study indicate that the policy of stopping the Football competition during the Covid-19 Pandemic has caused the club to experience financial problems due to the termination of the competition due to the decrease in incoming sponsors, and for players the impact on the economy of all players is disrupted because PSSI recommends each club to giving players only 25% salary, not only in terms of economy, the physical condition/fitness of players is also disrupted due to limited training grounds. Thus, the policy of stopping competition during the Covid-19 pandemic can work again in order to increase the club's finances and regenerate the economy of the entire Indonesian community, especially the economy of the players.